Case report: Rare epithelioid hemangioendothelioma occurs in both main bronchus and lung - Gong, Jiuyu; Tian, Fangfang; Wang, Qin; Mu, Mi; Geng, Sijia; Hao, Pengfei; Zhong, Pengfei; Zhang, Rui; Jiang, Lin; Wang, Rentao; Bao, Pengtao (Frontiers in Medicine, 2022)
Pulmonary epithelioid hemangioendothelioma (PEH) is a rare vascular tumor of endothelial origin with low- to intermediate-grade malignant potentials. Since there is no characteristic clinical or biological marker available for PEH, most cases require a surgical lung biopsy for diagnosis. To date, although some patients with PEH reported in the literature were diagnosed through bronchoscopic biopsy, most of the patients still underwent surgical lung biopsy for confirmation. In this case report, we present a rare case diagnosed as PEH through endobronchial biopsies due to the presence of an intraluminal mass that blocked the trachea and caused atelectasis in the right upper lobe. Moreover, since surgery was not appropriate for this patient with unresectable bilateral multiple nodules, we adopted genetic analysis using NGS to provide a guide for personalized treatment. Then, based on the NGS results, the patient was treated with anti-PD-1 mAb and sirolimus for 1 year and has been stable in a 1-year follow-up examination.